Flypaper Effect of General Allocation Funds and Regional Revenue in Central Java-Indonesia - Imtikhanah, Sobrotul; Astari; Fitrayudi, M (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2025)
Indonesia, with its 38 provinces, requires significant oversight and regulation by the central government. Decentralization offers a solution for managing numerous local governments, aiming to empower regions and ensure equitable development nationwide. Despite nearly a decade of decentralization, regions remain financially dependent on the central government. This study examines the flypaper effect as an indicator of decentralization's success, focusing on Central Java Province's regencies and cities, specifically the Ex-Pekalongan Residency area. The data utilized is financial statement of the Regional Government in the eks-Pekalongan Residency during the period spanning 2018 to 2023.The regression model was processed and tested using the SPSS program. It investigates (1) the impact of the General Goverment Allocation  and Regionally Sourced Income on regional expenditure, (2) which has a greater influence, (3) the presence of a flypaper effect, and (4) if the effect varies with high Regionally Original Income. The findings reveal that both income sources affect regional expenditure and that the flypaper effect persisted in Central Java from 2018-2023, even in regions with high original income.